A Clinical Study to Assess Pattern of Contrast Sensitivity Functions in Patients with Myopia - Thatte, Shreya; Monga, Ashima; Sharma, Haritima (BOHR International Journal of Current Research in Optometry and Ophthalmology, 2022)
The Covid-19 pandemic has posed a global threat to public health. In terms of affecting the systemic health, it has also created an impact on the ocular health of people. The scenario of work from home, long hours of online classes for students, has led to increase in incidences of refractive error. From affecting visual acuity, it has also posed increased risk of increasing the degree of myopia. Even in these cases a patient may have a best corrected visual acuity of 6/6 but he or she may not be satisfied due to improper contrast sensitivity. This study was done to compare contrast sensitivity functions in myopic patients by assessing and comparing various parameters such as demographic factors, age, sex and profession. We included 500 myopic patients with a best corrected visual acuity of 6/6, without any retinal pathology. Contrast sensitivity functions were compared with astigmatism, degree and duration of myopia and with duration of use of spectacles. All three age groups showed mild decline in contrast sensitivity but majority consisted of the under-30 age group with 233 cases (46.6%). Females being in majority (78.1%) had mild decrease in contrast sensitivity. We recorded the profession of each patient and observed that there was mild decline in contrast sensitivity in all professions, and 79.2% of the total students showed mild decrease in contrast sensitivity, which can be attributed to long hours of screen time in lockdown phase. Low myopia of less than 3D had mild decline in contrast sensitivity (88.4%), whereas severe decline in contrast sensitivity was seen in high myopics (11.9%), which was directly co-related with degree of myopia. Astigmatism also showed mild decline in contrast sensitivity, which was 78.5% in compound myopic astigmatism and 88.5% in simple myopic astigmatism. We found severe decline in contrast sensitivity only in 2.4% of myopic patients with a duration of less than 12 months. The rest of the patients had mild decline in contrast sensitivity. This validates that contrast sensitivity has an impact on all parameters of the study such as age, gender, profession, duration, degree of myopia and astigmatism